Dilatações vasculares intrapulmonares e síndrome hepatopulmonar na esquistossomose mansônica - Lima, Frederico Santana de (2012)
This study aimed at determining the prevalence of the hepatopulmonary syndrome (HPS) and intrapulmonary vascular dilation (IPVD), and how they relate to the arterial oxygenation, in schistosomotic patients with the hepatosplenic form (HSE). Method: Patients with HSE were submitted to arterial gasometry and contrast transthoracic echocardiogram (CTTE). Patients with IPVD were submitted to spirometry. The criteria to identify HSE patients were positive parasitological examination of feces and/or positive epidemiology and abdominal echography compatible with the hepatosplenic form of schistosomiasis, according to the Niamey criteria WHO. Patients with other liver diseases were excluded. Criterion for HPS: PaO2 < 80mmHg and/or AaPO2 ≥ 15 mmHg, IPVD diagnosed through CTEE, in adittion to schistosomotic portal hypertension. For the data analysis, the patients were classified under three groups: Group 1 Patients with HPS; Group 2 Patients with IPVD but no alterations in arterial oxygenation; Group 3 Patients without IPVD. Results: Seventeen out of forty patients (42.5%) presented IPVD, but only six met the criteria for HPS, showing a prevalence of 15%. Among those, only one HPS patient presented a level of PaO2 lower than 80 mmHg. The average age of the 40 schistosomotic patients was 48.6 years. No nail clubbing, spider nevi, or platypnea were observed. There was no relation between gender and presence of HPS or IPVD. PaO2 and AaPO2 medians differed significantly among the groups (P = 0.001 and P = 0.005, respectively). PaO2 was significantly higher in the group with IPVD while comparing to the group with no IPVD (P = 0.001). There was no significant difference while comparing the HPS group to the group with no IPVD (P = 0.957). AaPO2 was significantly lower in the group with IPVD while comparing to the group with no IPVD (P = 0.005). There was no significant difference while comparing the HPS group to the group with no IPVD (P = 0.381). Conclusion: The results indicate that the IPVD and PHS frequency in schistosomotic patients is similar to the one found in cirrhotic patients. The presence of IPVD does not correlate with alterations of the arterial oxygenation in patients with the hepatosplenic form of schistosomiasis. It is possible that changes in gas exchange are caused by other reasons unrelated to the presence of IPVD.